Online Representations of "Genome Editing" Uncover Opportunities for Encouraging Engagement: A Semantic Network Analysis. Issue 2 (April 2019) - Calabrese, Christopher; Anderton, Brittany N.; Barnett, George A.
Genome editing is an emerging socio-scientific issue. This study uses semantic network analysis to determine the concepts and frames the public is exposed to when seeking information about "genome editing" in Wikipedia and Google. Four frames were identified in Wikipedia: (1) methodology/terminology, (2) applications, (3) common approaches, and (4) DNA repair mechanisms. Three frames were identified in the Google webpages: (1) scientific contributions, (2) applications, and (3) methodology/terminology. Both representations of genome editing focused on technical information rather than social concerns. Most of the words in both networks were neutral in sentiment, suggesting an opportunity for encouraging engagement around this technology.